Proximate and Nutritional Content of Rainbow Trout (Oncorhynchus mykiss) Flesh Cultured in a Tropical Highland Area - Doan,Hien Van (2020)
Abstract The present study was performed to assess the proximate and nutrient content of rainbow trout flesh, cultured in the Doi Inthanon Fisheries Research Unit, Chiang Mai Inland Fisheries Research and Development Center, Thailand. 240 fish were randomly distributed across 12 cages with 20 fish cage-1. Sixteen individual fish from each cage were randomly collected at different ages of 10, 12 and 24 months. Body composition, pH, water-holding capacity, shear force, collagen content analysis, sensory, lipid oxidation, and fatty acids profile were evaluated. The results indicated that body composition and carcass length were significantly higher in fish aged 24 months, except for carcass and viscero-somatic index percentages (P ≤ 0.05). Fish at 24 months showed significantly higher pH, moisture, fat, shear force, thiobarbituric acid reactive substances, and total collagen content values than fish at 10 and 12 months (P ≤ 0.05). However, protein percentage, sensory measurement and water-holding capacity were significantly higher in younger fish at 10 and 12 months. The average lipid content and n-6/n-3 ratios were significantly greater in fish at 12 months and in ventral fillets (P ≤ 0.05). However, polyunsaturated fatty acids: saturated fatty acid ratio was higher in fish at 24 months and in dorsal fillets. In conclusion, rainbow trout cultured in sub-tropical, montane conditions can be valuable sources of protein, unsaturated fatty acids, eicosapentaenoic acids, and docosahexaenoic acids.